2021
DOI: 10.3389/fonc.2021.640881
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of an Integrative Prognostic Model of Radiogenomics Features With Underlying Gene Expression Patterns in Clear Cell Renal Cell Carcinoma

Abstract: BackgroundClear cell renal cell carcinoma (ccRCC) is one of the most common malignancies in urinary system, and radiomics has been adopted in tumor staging and prognostic evaluation in renal carcinomas. This study aimed to integrate image features of contrast-enhanced CT and underlying genomics features to predict the overall survival (OS) of ccRCC patients.MethodWe extracted 107 radiomics features out of 205 patients with available CT images obtained from TCIA database and corresponding clinical and genetic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Recent studies have reported that the initial treatment response is an indicator of a favorable clinical prognosis, such as better progression-free survival and overall survival (8)(9)(10)(11). However, the development of a precise model for predicting the initial response to TACE therapy is desired, and radiomics is a promising method that involves the extraction of several quantitative features from radiology images, which could be feasibly used (12,13). Previous studies have shown that conventional machine learning (cML) based on radiomics could be used to significantly predict clinical outcomes in cancers (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that the initial treatment response is an indicator of a favorable clinical prognosis, such as better progression-free survival and overall survival (8)(9)(10)(11). However, the development of a precise model for predicting the initial response to TACE therapy is desired, and radiomics is a promising method that involves the extraction of several quantitative features from radiology images, which could be feasibly used (12,13). Previous studies have shown that conventional machine learning (cML) based on radiomics could be used to significantly predict clinical outcomes in cancers (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Our study has filled a gap in the literature on PFS risk of stage I-III RCC in the setting of radiomics. In the recent literature, Radiomics nomogram has demonstrated excellent efficacy in differential diagnosis, nuclear grading, prognosis, and gene expression of RCC (38)(39)(40)(41)(42)(43). Among the 6 RFs selected in this study, there were 3 features from the corticomedullary phase, suggesting that the corticomedullary phase may contain more abundant information to predict PFS.…”
Section: Discussionmentioning
confidence: 90%
“…Class 3 had higher FBN2 expression, which has been previously associated with improved overall survival [52,53]. Finally, Huang et al [26] unearthed a gene expression module (comprised of 256 genes) that was associated with four selected radiomic features (75% higher-order) derived from 205 ccRCC patients from the TCIA. These genes mediate tumor angiogenesis, cell adhesion, and extracellular structure organization.…”
Section: Beyond Mutations In Common Pathogenic Single Genes In Clear ...mentioning
confidence: 99%
“…Additionally, Yin et al [22] showed that a model combining radiomic and clinical features (tumor size; stage; and grade) outperformed a radiomics only model in predicting ccRCC molecular subtype (91.3% vs. 86.96% accuracy). Finally, Huang et al [26] developed an integrative nomogram of ccRCC survival incorporating tumor stage, gender, and a risk score incorporating both prognostic radiomic and genetic factors.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%